Association of diabetes risk with changes in memory, working memory, and processing speed among older adults - Lee, Jungjoo; Kim, Junhyoung; An, Sang Joon (Frontiers in Psychology, 2024)
Background: This study investigated the risk of diabetes by examining changes in memory, working memory, and processing speed among older adults to provide evidence on how each cognitive domain is associated with the risk of diabetes in older adults. Methods: This study used Health and Retirement Study data and tracked the respondents from 2012 to 2020 (n = 5,748). The Telephone Interview for Cognitive Status-27 includes three cognitive tests (recall, seven subtraction, and counting backward tests) to assess each cognitive domain. A Cox Proportional Hazard Regression was employed to calculate the changes in the Odds Ratio (OR) of diabetes by increasing each cognitive function and the parameter in covariates.Results: We found that the OR of diabetes decreased with increasing universal cognitive function, increasing memory, working memory, and processing speed, and that age increased the OR in all analysis models.Conclusions: The findings of this study contribute to filling gaps in the literature by exploring:(a) the association between each cognitive function and the decline in diabetes risk, and (b) the varying patterns of change in diabetes risk with increasing cognitive function.